Self-compacting concrete and preparation method thereof

Through the mixing of materials of specific ratios, an improved self-condensing concrete was prepared, which solved the problem of early self-shrinking, large, and prone to cracks not being tightly combined with the steel plate, and achieved the effect of reducing hydration heat, dense internally, and tightly combining with the steel plate.

CN119707395APending Publication Date: 2025-03-28SICHUAN CHINA NUCLEAR POWER ENG INSPECTION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411899961.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing self-solid concrete has large self-shrinkage in the early stage, is prone to cracks, and is not closely linked to steel plates.

Method used

By mixing cement, fly ash, mineral powder, expansion agent, sand, gravel, water reducing agent and water with specific ratios, a self-finished concrete is prepared, which reduces the amount of cement, reduces the hydration heat, improves the density of the concrete and the bonding density with the steel plate.

Benefits of technology

The hydration heat of concrete is reduced, no cracks inside, and close bonding with steel plates, reducing self-shrinkage and dry shrinkage, and reducing cement usage and unilateral cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707395A_ABST
    Figure CN119707395A_ABST
Patent Text Reader

Abstract

The invention discloses self-compacting concrete and a preparation method thereof, and relates to the field of engineering construction. The self-compacting concrete is prepared from the following raw materials in parts by weight: 300 to 400 parts of cement, 50 to 100 parts of fly ash, 50 to 100 parts of mineral powder, 50 to 100 parts of expanding agent, 100 to 900 parts of sand, 700 to 900 parts of gravel, 4 to 6 parts of water reducing agent and 160 to 180 parts of water. The cement, the fly ash, the mineral powder, the expanding agent, the sand, the broken stone, the water reducing agent and the water are mixed according to a specific ratio, so that the hydration heat of the obtained concrete is obviously reduced, no crack exists in the concrete, the use amount of the cement can be reduced by 10-20%, and meanwhile, the cost of the concrete per cubic meter is also reduced; the autogenous shrinkage of the concrete is obviously reduced, and the autogenous shrinkage is changed into micro-expansion from shrinkage; and meanwhile, the self-compacting concrete and the steel plate are free from a disengagement phenomenon, so that the compactness of combination with the steel plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of engineering construction, and in particular to a self-compacting concrete and a preparation method thereof. Background Art

[0002] The nuclear power development strategy is an important part of my country's power development strategy and national energy security strategy. With the advancement of the marketization process, many buildings have put forward higher and higher requirements for shortening construction period, reducing project cost and improving project quality. In order to meet market demand, a large number of modular steel plate concrete technologies will be adopted to shorten construction period and improve construction efficiency. However, the internal structure of the module is complex and there are many obstacles. Most modules are more than 10 meters deep, which makes it difficult to pour ordinary concrete and control quality. The height of the steel module is too large, which makes it difficult for the vibrator to descend to the specific position, and ordinary concrete is difficult to meet the requirements. Self-compacting concrete is a high-performance concrete that can automatically fill the module to form a uniform and dense concrete structure, and effectively avoid quality problems caused by under-tamping, missed vibration or over-vibration. It can also save labor costs, speed up construction progress and shorten the construction period.

[0003] However, when designing the mix ratio of existing steel plate self-compacting concrete, fly ash is generally added alone. Since self-compacting concrete has many cementitious materials, the amount of cement used is very large, and the hydration heat of concrete is very large. At the same time, since the outer side is a steel plate, the heat transfer effect is good, and it is difficult to control the cooling rate of large-volume concrete, and the probability of internal cracks is very high. The fit between the steel plate and the concrete mainly depends on the anchor nails on the inner side of the steel plate. If the self-compacting concrete has a large early autogenous shrinkage, the low bond strength between the concrete and the anchor nails in the early stage cannot effectively resist the autogenous shrinkage of the concrete. Through elastic wave CT scanning, the current single-mixed self-compacting concrete and the steel plate have a phenomenon of decoupling, and the steel plate and concrete are not tightly combined. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the existing self-compacting concrete has large early self-shrinkage, is prone to cracking, and is not tightly bonded to the steel plate.

[0005] One of the purposes is to provide a self-compacting concrete, which solves the problems of large early self-shrinkage, easy cracking and loose bonding with steel plates.

[0006] The second purpose is to provide a method for preparing a self-compacting concrete to prepare the above-mentioned self-compacting concrete.

[0007] The present invention is achieved through the following technical solutions:

[0008] A self-compacting concrete comprises the following raw materials in parts by weight: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of mineral powder, 50-100 parts of expansion agent, 100-900 parts of sand, 700-900 parts of crushed stone, 4-6 parts of water reducing agent and 160-180 parts of water.

[0009] As a possible design, the self-compacting concrete includes the following raw materials in parts by weight: 330-380 parts of cement, 60-80 parts of fly ash, 6-80 parts of mineral powder, 60-80 parts of expansion agent, 300-700 parts of sand, 750-850 parts of crushed stone, 4.5-5.5 parts of water reducer and 165-175 parts of water.

[0010] As a possible design, the fineness modulus of the above-mentioned sand is 2.6 to 3.0.

[0011] As a possible design, the sand has a stone powder content of 2.6-6.8%, a mud content of 0.1-0.2%, and a continuous loose bulk density of 1480-1550 kg / m 3 , apparent density is 2620~2630kg / m 3 , firmness is 3.1~3.4%.

[0012] As a possible design, the needle-like content of the above-mentioned gravel is 0.8-1.2%.

[0013] As a possible design, the gravel size is 5 to 16 mm.

[0014] As a possible design, the fly ash fineness is 6-7%.

[0015] As a possible design, the alkali content of the above-mentioned expansion agent is 0.7-0.8 g / cm 3 .

[0016] As a possible design, the expansion agent is a magnesium expansion agent, and the water reducer is a polycarboxylic acid high-performance water reducer.

[0017] The present invention also provides a method for preparing self-compacting concrete, comprising the following steps:

[0018] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0019] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] The invention can significantly reduce the hydration heat of the obtained concrete by mixing cement, fly ash, mineral powder, expansion agent, sand, crushed stone, water reducing agent and water in a specific ratio, and has no internal cracks. The cement dosage can be reduced by 10%-20%, and the unit cost of concrete is also reduced. The autogenous shrinkage of concrete is significantly reduced, and the autogenous shrinkage in 3 days is reduced by 100×10 -6 becomes -100×10 -6 , 56 days shrinkage from 400×10 -6 becomes 300×10 -6 , the autogenous shrinkage changes from shrinkage to slight expansion, and the shrinkage decreases by 100×10 -6 At the same time, there is no gap between the self-compacting concrete and the steel plate, which improves the tightness of the combination with the steel plate.

[0022] The present invention not only has the superior characteristics of self-compacting concrete, but is also economical, efficient, energy-saving and environmentally friendly. It can be used in nuclear power projects, as well as in civil construction, roads and bridges, water conservancy and other fields. The addition of mineral powder and fly ash to concrete will greatly reduce the hydration heat of concrete. It can also be used as ordinary concrete, reduce noise pollution, reduce occupational health damage of vibration workers, and reduce the comprehensive cost of concrete, and has a broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0024] Figure 1 is a compressive strength curve diagram of Example 2;

[0025] Figure 2 This is a graph showing the compressive creep test results at different ages of Example 3. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0027] The existing self-compacting concrete has the problems of large cement consumption, large concrete hydration heat, slow cooling speed, easy internal cracks and loose bonding with steel plates.

[0028] Based on this, the present invention provides a self-compacting concrete, comprising the following raw materials in parts by weight: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of mineral powder, 50-100 parts of expansion agent, 100-900 parts of sand, 700-900 parts of crushed stone, 4-6 parts of water reducer and 160-180 parts of water.

[0029] The present invention adds fly ash, which contains more than 70% glass microspheres. These microspheres have complete particle shapes and smooth surfaces, and are dense in texture. This form reduces water, makes concrete dense and homogenous, and is conducive to promoting the depolymerization of the initial cement hydration reaction. At the same time, it improves the rheological properties and initial structure of the mixing material, as well as the various functions of the concrete after hardening, and can provide a good lubrication effect. It also contains a large amount of active SiO2 and Al2O3, which react chemically with alkaline substances such as Ca(OH)2 in a humid environment to generate cementitious substances such as hydrated calcium silicate and hydrated calcium aluminate, which can enhance the fly ash products and concrete, block the capillary structure in the concrete, and improve the corrosion resistance of the concrete. The very small micro-beads and debris in fly ash can be equivalent to unhydrated cement particles in cement paste. The extremely fine micro-beads are equivalent to active nanomaterials. They are evenly distributed in the cement slurry, filling pores and capillaries, improving the pore structure of concrete and increasing the density. They can significantly improve and enhance the structural strength of concrete and its products, and improve the homogeneity and density.

[0030] Slag can exert micro-aggregate effect, micro-crystal nucleus effect, volcanic ash effect, improve impermeability, reduce hydration heat, and prevent temperature rise cracks. First, since concrete can be regarded as a continuously graded particle stacking system, the gaps between coarse aggregates are filled by fine aggregates, the gaps between fine aggregates are filled by cement particles, and the gaps between cement particles require finer particles to fill. According to the Aim and Goff model theory, when the cement-based material system with ultrafine mineral admixtures is regarded as a multi-element system, there is a most compact stacking in the system. The fineness of slag powder is finer than that of cement particles. After replacing part of the cement, these small particles fill in the gaps between cement particles, making the cementitious material have a better gradation, forming a dense filling structure and a self-compacting stacking system at the microscopic level. At the same time, it can also reduce the water consumption under standard consistency, and increase fluidity while maintaining the same water consumption, thereby improving workability. Another benefit of the filling effect is that it increases cohesion, prevents water segregation, and improves pumpability. Second, slag plays a role of microcrystalline nucleus effect for cement hydration system, accelerates the progress of cement hydration reaction and provides ample space for hydration products, improves the uniformity of cement hydration product distribution, makes cement stone structure more compact, and thus makes concrete have better mechanical properties. Third, slag powder is added to concrete. In the alkaline environment inside concrete, slag powder absorbs Ca(OH)2 formed during cement hydration, and can promote cement further hydration to produce more favorable CSH gel, making Ca(OH)2 grains in aggregate interface area smaller, improving concrete microstructure, significantly reducing the porosity of cement paste, strengthening aggregate interface bonding, and greatly improving the physical and mechanical properties of concrete. Fourth, slag replaces part of cement and reduces the internal cause of erosion. At the same time, when slag powder is evenly dispersed in cement paste, it forms the core of hydration products. Slag powder added to concrete can absorb part of Ca(OH)2 to produce secondary hydration reaction. Hydration products further fill the structural pores, making the structure denser and more impermeable. Fifth, in the initial stage of cement hydration, heat release is concentrated, which will cause slump loss. After the slag powder is added, since it cannot be directly hydrated by itself, it can only be secondary hydrated under the alkaline conditions of cement hydration. Therefore, it can delay the hydration heat release, and the initial slump can be maintained longer, reducing temperature cracks caused by temperature rise.

[0031] In addition, fly ash and slag powder are added to concrete to improve the particle gradation of powder materials, reduce the porosity of cementitious material system, and make the composition of cementitious material system denser. The two admixtures give full play to their respective micro-aggregate effect and volcanic ash effect. The multiple effects are superimposed on each other, making the structure of cement paste denser, improving various properties of concrete, and showing certain filling effect, morphological effect, volcanic ash effect and interface coupling effect. This is due to the differences in particle gradation, particle size, particle morphology and mineral composition, which can fill each other and play a positive effect of reducing porosity and improving density.

[0032] Expansive agents expand the volume of concrete through physical and chemical effects, thereby improving the void structure.

[0033] The three additives of fly ash, slag powder and expansion agent in concrete can produce a superimposed effect, which is mainly manifested in improving the strength, durability and work performance of concrete. This superimposed effect is caused by the characteristics and action mechanism of the three additives: fly ash and slag powder are used as admixtures to fill the pores of concrete, improve the density and impermeability of concrete, and participate in the hydration reaction to enhance the strength of concrete; while the expansion agent improves the structure of concrete by filling the microscopic pores inside the concrete, reduces the risk of temperature and age cracking, and makes the concrete more stable and durable. Within the proportion range of the present invention, the three act on concrete at the same time, can be superimposed on each other to enhance their respective effects, and comprehensively improve the overall performance of concrete. Specifically, first, the active ingredients in fly ash and slag powder react with cement to form additional hydration products, which enhance the cohesion and bonding force of concrete and improve the compressive strength of concrete; the expansion agent improves the structure of concrete by filling the microscopic pores in concrete, improves the compactness of concrete, and further increases the compressive strength of concrete. Second, the fine particles in fly ash and slag powder fill the pores in concrete, reducing the permeability of concrete, reducing the penetration of moisture and harmful substances, and improving the impermeability and durability of concrete; the expansion agent can fill the micro cracks and pores in concrete, reducing the cracking and shrinkage of concrete over time, and extending the service life of concrete structures. Third, the addition of fly ash and slag powder can slow down the hydration reaction rate of concrete, reduce the temperature rise rate of concrete, and reduce the risk of temperature cracks in concrete; the addition of expansion agent can reduce the temperature sensitivity of concrete and reduce the risk of shrinkage and cracking of concrete in high and low temperature environments. Fourth, the addition of fly ash and slag powder can improve the fluidity and plasticity of concrete, improve the working performance and molding performance of concrete; the addition of expansion agent can improve the fluidity of concrete, reduce the viscosity of concrete, and improve the pumping performance and construction performance of concrete.

[0034] Water reducing agent can improve the fluidity, cohesion and filling properties of concrete.

[0035] Preferably, the cement is silicate cement. The silicate cement is a cement with low tricalcium aluminate and low standard consistency water consumption.

[0036] In some embodiments of the present invention, the expansion agent is a magnesium expansion agent; and the water reducing agent is a polycarboxylic acid high-performance water reducing agent.

[0037] In some embodiments of the present invention, the self-compacting concrete comprises the following raw materials in parts by weight: 330-380 parts of cement, 60-80 parts of fly ash, 60-80 parts of mineral powder, 60-80 parts of expansion agent, 300-700 parts of sand, 750-850 parts of crushed stone, 4.5-5.5 parts of water reducer and 165-175 parts of water.

[0038] In some embodiments of the present invention, the fineness modulus of the sand is 2.6-3.0.

[0039] The inventors have found that if the sand is too fine, the mechanical properties of concrete, such as strength and elastic modulus, will be adversely affected; at the same time, the large specific surface area of ​​fine sand will increase the amount of water used, affecting the working performance of concrete. If coarse sand is used, the cohesiveness of concrete will be reduced, and segregation will easily occur. Therefore, choosing sand with a fineness modulus of 2.6 to 3.0 can not only improve the strength and elastic modulus of concrete, but also have a certain fluidity and reduce the amount of water in concrete.

[0040] Preferably, the porosity of the sand is 41-42%. When the porosity is within this range, the compactness of the prepared concrete is better, and the voids and cracks in the concrete can be reduced, thereby improving the strength of the concrete.

[0041] In some embodiments of the present invention, the sand has a stone powder content of 2.6-6.8%, a mud content of 0.1-0.2%, and a continuous loose bulk density of 1480-1550 kg / m 3 , apparent density is 2620~2630kg / m 3 , firmness is 3.1~3.4%.

[0042] Preferably, the mica content of the above-mentioned sand is 0.2-0.5%, the light matter content is not more than 0.1%, the chloride ion content is not more than 0.001%, the water absorption rate is 0.7-1.8%, the alkali activity is less than 0.09%, and the sulfide and sulfate content is not more than 0.2%.

[0043] In some embodiments of the present invention, the needle-like content of the above-mentioned gravel is 0.8-1.2%.

[0044] The inventors have found that the content of needle-like particles in crushed stone directly affects the flowability and gap passing performance of concrete, because it will increase the porosity, increase the amount of mortar required under the same working performance requirements, affect the compactness of concrete, and be unfavorable to the improvement of mechanical properties and long-term durability. Selecting crushed stone with a needle-like content within the above range can improve the workability and durability of concrete.

[0045] In some embodiments of the present invention, the size of the gravel is 5 to 16 mm.

[0046] In some embodiments of the present invention, the fly ash has a fineness of 6-7%.

[0047] The fineness of fly ash has a significant impact on the performance of concrete. Fly ash particles that are too fine will reduce the compressive strength and durability of concrete, while increasing the risk of shrinkage and cracking of concrete; while fly ash particles that are too coarse will affect the fluidity and workability of concrete, causing concrete to easily segregate. By selecting fly ash with the above fineness, it is beneficial to improve the workability of fresh concrete and the durability of hardened concrete.

[0048] Preferably, the 7-day activity index of the mineral powder is 85-90%, and the 28-day activity index is 125-135%.

[0049] Preferably, the 7-day compressive strength ratio of the water reducing agent is 215-225%, and the 28-day compressive strength ratio is 160-170%.

[0050] In some embodiments of the present invention, the alkali content of the above-mentioned expansion agent is 0.7-0.8 g / cm 3 .

[0051] The present invention also provides a method for preparing self-compacting concrete, comprising the following steps:

[0052] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0053] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0054] Example 1

[0055] A method for preparing self-compacting concrete comprises the following steps:

[0056] Raw materials: 300kg cement, 50kg fly ash, 50kg mineral powder, 50kg expansion agent, 100kg sand, 700kg gravel, 4kg water reducer and 160kg water.

[0057] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0058] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0059] Example 2

[0060] A method for preparing self-compacting concrete comprises the following steps:

[0061] Raw materials: 330kg cement, 60kg fly ash, 60kg mineral powder, 60kg expansion agent, 300kg sand, 750kg gravel, 4.5kg water reducer and 165kg water.

[0062] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0063] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0064] Example 3

[0065] A method for preparing self-compacting concrete comprises the following steps:

[0066] Raw materials: 380kg cement, 80kg fly ash, 80kg mineral powder, 80kg expansion agent, 700kg sand, 850kg gravel, 5.5kg water reducer and 175kg water.

[0067] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0068] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0069] Example 4

[0070] A method for preparing self-compacting concrete comprises the following steps:

[0071] Raw materials: 400kg cement, 100kg fly ash, 100kg mineral powder, 100kg expansion agent, 900kg sand, 900kg gravel, 6kg water reducer and 180kg water.

[0072] Dissolve the water reducing agent and the expansion agent in water to prepare a solution;

[0073] Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.

[0074] Comparative Example 1

[0075] It is basically the same as Example 2, except that no expansion agent is added.

[0076] Experimental example

[0077] (I) Example 2 and Comparative Example 1 were subjected to a concrete mixing performance test and a concrete hardening performance test. The results are shown in Tables 1 and 2.

[0078] Table 1

[0079] Test items Design requirements Example 2 Comparative Example 1 Concrete temperature(℃) / 20.2 20.5 <![CDATA[Unit weight (kg / m 3 )]]> 2350 2360 2370 Slump expansion (mm) 700±50 680 685 J ring clearance (mm) 0~25 4.7 4.2 <![CDATA[T 500 (s)]]> 2~8 4.7 4.2 Gas content (%) ≤4 2.2 2.6 Segregation rate (%) ≤15 4.5 4.9 V Funnel passing time (S) 4~20 13.2 11.8 U-shaped box filling height (mm) ≥320 340 330

[0080] Table 2

[0081]

[0082] Observe Table 1-2 and Figure 1 It can be seen that the comprehensive performance of the concrete obtained in Example 2 of the present invention is better.

[0083] (II) The concrete of Example 3 was subjected to mechanical property test and compressive creep test. The mechanical property test results are shown in Table 3 and Figure 1 The results of the compression creep test are shown in Table 4 and Figure 2 shown.

[0084] Table 3

[0085]

[0086] Table 4

[0087] Age Creep Creep coefficient Age Creep Creep coefficient 1d <![CDATA[2.218×10 -6 / MPa]]> 0.071 60d <![CDATA[11.230×10 -6 / MPa]]> 0.358 3d <![CDATA[4.200×10 -6 / MPa]]> 0.134 90d <![CDATA[12.230×10 -6 / MPa]]> 0.390 7d <![CDATA[6.184×10 -6 / MPa]]> 0.197 120d - - 14d <![CDATA[7.528×10 -6 / MPa]]> 0.240 150d - - 28d <![CDATA[9.391×10 -6 / MPa]]> 0.299 180d - - 45d <![CDATA[10.552×10 -6 / MPa]]> 0.336 / - -

[0088] Example 3 has excellent mechanical properties and good compressive creep performance.

[0089] The invention can significantly reduce the hydration heat of the obtained concrete by mixing cement, fly ash, mineral powder, expansion agent, sand, crushed stone, water reducing agent and water in a specific ratio, and has no internal cracks. The cement dosage can be reduced by 10%-20%, and the unit cost of concrete is also reduced. The autogenous shrinkage of concrete is significantly reduced, and the autogenous shrinkage in 3 days is reduced by 100×10 -6 becomes -100×10 -6 , 56 days shrinkage from 400×10 -6 becomes 300×10 -6 , the autogenous shrinkage changes from shrinkage to slight expansion, and the shrinkage decreases by 100×10 -6 At the same time, there is no gap between the self-compacting concrete and the steel plate, which improves the tightness of the combination with the steel plate.

[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A self-compacting concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of mineral powder, 50-100 parts of expansion agent, 100-900 parts of sand, 700-900 parts of crushed stone, 4-6 parts of water reducing agent and 160-180 parts of water.

2. A self-compacting concrete according to claim 1, characterized in that: The self-compacting concrete comprises the following raw materials in parts by weight: 330-380 parts of cement, 60-80 parts of fly ash, 6-80 parts of mineral powder, 60-80 parts of expansion agent, 300-700 parts of sand, 750-850 parts of crushed stone, 4.5-5.5 parts of water reducing agent and 165-175 parts of water.

3. The self-compacting concrete according to claim 1, characterized in that: The fineness modulus of the sand is 2.6 to 3.

0.

4. The self-compacting concrete according to claim 1, characterized in that: The sand has a stone powder content of 2.6-6.8%, a mud content of 0.1-0.2%, and a continuous loose bulk density of 1480-1550 kg / m 3 , apparent density is 2620~2630kg / m 3 , firmness is 3.1~3.4%.

5. The self-compacting concrete according to claim 1, characterized in that: The needle-like content of the crushed stone is 0.8-1.2%.

6. The self-compacting concrete according to claim 1, characterized in that: The crushed stone has a size of 5 to 16 mm.

7. The self-compacting concrete according to claim 1, characterized in that: The fly ash fineness is 6-7%.

8. The self-compacting concrete according to claim 1, characterized in that: The alkali content of the expansion agent is 0.7-0.8 g / cm 3 .

9. The self-compacting concrete according to claim 1, characterized in that: The expansion agent is a magnesium expansion agent, and the water reducing agent is a polycarboxylic acid high-performance water reducing agent.

10. A method for preparing a self-compacting concrete according to any one of claims 1 to 9, characterized in that: The steps include: Dissolve the water reducing agent and the expansion agent in water to prepare a solution; Add cement, fly ash, mineral powder and sand into the solution, stir evenly, and finally add crushed stone and stir to obtain self-compacting concrete.